An inclusive solution based on grey water footprint for performance evaluation of industrial wastewater treatment systems - Keivan Arastou; Ali Dehnavi; Shervin Jamshidi (Scientific Reports)
Abstract This study developed a new framework based on grey water footprint (GWF) to inclusively evaluate and compare the industrial wastewater treatment plants (WWTPs). The conventional approach typically reports the efficiency of treatment systems on abating the concentration of each pollutant, individually. As an alternative, GWF can simultaneously include multiple pollutants, pollution loads, and regional water quality standards in calculations. These advantages are critical for assessing an industrial WWTP treating complex wastewater, with hazardous pollutants and variable inflow. Moreover, we introduced four innovative criteria based on GWF and improved it as a multi-functional index. To verify the applicability of the proposed method, we chose two operating units in parallel, the activated sludge (AS) and membrane bioreactor (MBR), as case studies treating real industrial wastewater. Samples were obtained from both treated and untreated wastewater. 36 pollutants were examined and used for GWF accounting in different scenarios. These scenarios were based on different maximum allowable concentrations (Cmax). Multi-pollutant GWF reduction (%) was the first index evaluating the overall removal efficiency. The AS with 93.1% average GWF removal could outperform MBR with 87.1% removal. Operational reliability was the second index, showed that AS could reduce GWF variations from inlet to the outlet with 83.7% efficiency, while it was 77.5% for MBR. The third index was GWF per carbon footprint (GWCF). It quantified the equivalent abated stress from water bodies per increased pressure exerted by emitting greenhouse gas (GHG) during wastewater treatment. The GWCF of AS was 347.8 m3/kg-CO2 indicating a superior efficiency over MBR with 84.9 m3/kg-CO2. It means that MBR relatively emitted more GHGs for reducing less GWF. Heavy metal pollution reduction (HPI) was the fourth index quantified based on GWF. It evaluated the particular performance of treatment systems for abating hazardous pollutants. The AS with an average HPI of 56.7% outperformed MBR with 50.4% efficiency. Therefore, this study showed that GWF is a versatile and applicable index and can provide a more holistic framework for evaluating and comparing wastewater treatment units.